1979
DOI: 10.1111/j.1365-3091.1979.tb00917.x
|View full text |Cite
|
Sign up to set email alerts
|

A geochemical and mineralogical investigation of some British and other European tonsteins

Abstract: The volcanic origin of a number of major tonstein horizons has been established from mineralogical compositions and from trace elements that are quantitatively retained during diagenesis. Discriminant function analysis using the variables Ti/Al, Cr/Al, Zr/Al and Ni/Al allows the tonsteins to be classified according to original composition. Two main groups are recognized amongst the British tonsteins. Those formed from acid volcanic ash are comparable in composition with French and German tonsteins and a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 16 publications
2
43
0
1
Order By: Relevance
“…As described by Spears [56,57], Dai et al [58,59], Zhou et al [60] and Zhao et al [43], "tonsteins" are partings derived from air-borne material of pyroclastic origin in the peat-forming environment. They have been found in some coal seams of SW China [15,43,[58][59][60].…”
Section: Volcanic Ash Inputmentioning
confidence: 99%
“…As described by Spears [56,57], Dai et al [58,59], Zhou et al [60] and Zhao et al [43], "tonsteins" are partings derived from air-borne material of pyroclastic origin in the peat-forming environment. They have been found in some coal seams of SW China [15,43,[58][59][60].…”
Section: Volcanic Ash Inputmentioning
confidence: 99%
“…Based on bed thickness and grain size variations, Bouroz (1967) suggested that Westphalian tonsteins within the Nord-Pas de Calais and Saar-Lorraine basins were derived from the southeast, possibly from the Vosges Massif or Black Forest. Subsequently, Spears & Kanaris-Sotiriou (1979) correlated several Westphalian tonsteins in the Pennine Basin, United Kingdom, with tonsteins in the Nord-Pas de Calais and Ruhr basins, and hypothesised that they shared a common volcanic source. Spears & O'Brien (1994) elaborated on this by suggesting that the British tonsteins were sourced from volcanoes related to I-type granitic plutons within the Variscan orogenic belt.…”
Section: Comparison To Late Baskhirian To Moscovian Tonsteins Of Westmentioning
confidence: 99%
“…Bouroz, 1967;Fiebig, 1967;Spears & Kanaris-Sotiriou, 1979;Delcambre, 1987Delcambre, , 1996. Based on trace element geochemistry, felsic Westphalian tonsteins of the Pennine, Campine and Ruhr basins were originally subalkaline, intermediate to felsic ashes (Fig.…”
Section: Comparison To Late Baskhirian To Moscovian Tonsteins Of Westmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been made to chemically identify the parent material of altered vitric ashfalls, particularly bentonites and tonsteins, but these have been unsuccessful or greatly compromised (Spears and Kanaris-Sotiriou, 1979;Schmincke et al, 1982;Fisher and Schmincke, 1984). Similarly, because the layers of the K/T boundary unit have been extensively altered, we can only infer some generalization on original glass compositions.…”
Section: Alteration Of Original Vitric Materials and Clay-mineral Genmentioning
confidence: 99%